Rationalising government fiscal reporting Lessons learned from Australia, Canada, France and the United Kingdom on how to better address users' needs - Moretti, Delphine (OECD Publishing, 2018)
In OECD countries, fiscal reports are increasingly sophisticated, highlighting governments' commitment to fiscal transparency and accountability towards parliaments and citizens. However, users regularly express concerns with these documents, revealing a fundamental "paradox" with government fiscal reporting: desire for detail and sophistication may come at the expense of clarity. Against this background, this paper looks at four countries (Australia, Canada, France and the United Kingdom) that have endeavoured to resolve this paradox by rationalising their fiscal reporting with the aim of making it more legible for users and draws a short set of implications for other countries looking to strengthen and rationalise their fiscal reporting practices. JEL Codes: H50, H60, H83 Keywords: fiscal reporting, accountability, transparency
Keywords: Finance and Investment; Governance; Economics